GEOMECHANICAL STRESS PROFILE AT GUNDIH FIELD: STRESS QUANTIFICATION AND ANALYSIS IN RESERVOIR FOR CO2 INJECTION - Harya Danio; Benyamin Sapiie; Oddy Adnan; Takeshi Tsuji; Mohammad Rachmat Sule (PETRO:Jurnal Ilmiah Teknik Perminyakan, 2019)
Geomechanical analysis is performed at Gundih Field to obtain detail stress condition and mechanical properties from interval of interest. Ngrayong Formation is targeted as CO2 injection interval of Gundih Field. The detail interval 8 is determined using multi-mineral modelling and calibrated using XRD and petrographic data. Overpressure is detected from this well at Ngrayong Formation. Stress direction from adjacent well showed NE – SW direction of maximum horizontal stress. Stress magnitudes and mechanical properties are calculated using available log data through well-established empirical equation resulted thrust faulting regime acting on this area. Injection capability of formation is examined from Mohr – Coulomb diagram with input from calculated stress.Keywords: Geomechanics; Gundih Field; Ngrayong Formation; Reservoir; overpressure.